Perancangan Interior Fasilitas Restoran Mahameru di Surabaya - Danny Christopher Simon; Andereas Pandu Setiawan; Poppy Firtatwentyna Nilasari (Intra, 2017)
Food is one of the basic human needs and hence restaurants, such as Mahameru Restaurant in Surabaya, are designed to meet this need. This thesis project aims to redesign Mahameru restaurant with the concept of promoting the abundance and magnificence of Indonesian marine through the application of an aquarium as interior element and supplemented by visual information regarding the population and habitat of Indonesian fishery. The concept is inspired by sea and mountains (as depicted in the logo of Mahameru Restuarant), and hence the theme is named